Synthesis, reactivity and preliminary biological activity of iron(0) complexes with cyclopentadienone and amino‐appended N‐heterocyclic carbene ligands. (3rd March 2019) - Cingolani, Andrea; Zanotti, Valerio; Zacchini, Stefano; Massi, Massimiliano; Simpson, Peter V.; Maheshkumar Desai, Nima; Casari, Ilaria; Falasca, Marco; Rigamonti, Luca; Mazzoni, Rita
Abstract : Neutral and cationic cyclopentadienone (CpO) N ‐heterocyclic carbene (NHC) bis ‐carbonyl iron(0) complexes bearing, appended to the NHC ligand, either a terminal amino group on the lateral chain, [Fe(η 4 ‐CpO)(CO)2 (κ C ‐NHC(CH2 ) n NH2 )] with n = 2 (2a ) and 3 (2b ), or a cationic NMe3 + fragment, [Fe(η 4 ‐CpO)(CO)2 (κ C ‐NHC(CH2 )2 NMe3 )](I) (3 ), were prepared and characterized in terms of their structure, stability and reactivity. The photochemical properties of2a and2b were examined both in organic solvents and in water, revealing the photoactivated release of one CO ligand followed by the formation of the chelated complex [Fe(η 4 ‐CpO)(CO)(κ 2 C, N ‐NHC(CH2 )2 NH2 )] (4 ), whose molecular structure was confirmed by single crystal X‐ray diffraction studies. This metallacyclization occurs only in the case of2a, with the ethylene spacer between NHC ring and NH2 group in the lateral chain, allowing the formation of a stable 6‐membered ring. On the other hand, 2b undergoes decomposition upon irradiation. The reactivity in aqueous solutions revealed the chemical speciation of the complexes at different pH and especially under physiological conditions (phosphate buffer solution at pH 7.4 and 37 °C). The lack of data on the biological properties of iron(0) complexes prompted us to preliminarily investigate their cytotoxicity against model cancer cells (AsPC‐1 and HPAF‐II), along with a determination of their lipophilicity. Abstract : Cyclopentadienone iron(0) complexes bearing an amino functionality on the lateral chain of the ancillary N‐heterocyclic carbene ligand show cytotoxicity properties against pancreatic cancer AsPC‐1 and HPAF‐II cells comparable to carboplatin.